Two-dimensional non-carbon materials-based electrochemical printed sensors: an updated review - Falina, Shaili; Anuar, Khairu; Shafiee, Saiful Arifin; Juan, Joon Ching; Manaf, Asrulnizam Abd; Kawarada, Hiroshi; Syamsul, Mohd (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Recently, there has been increasing interest in electrochemical printed sensors for a wide range of applications such as biomedical, pharmaceutical, food safety, and environmental fields. A major challenge is to obtain selective, sensitive, and reliable sensing platforms that can meet the stringent performance requirements of these application areas. Two-dimensional (2D) nanomaterials advances have accelerated the performance of electrochemical sensors towards more practical approaches. This review discusses the recent development of electrochemical printed sensors, with emphasis on the integration of non-carbon 2D materials as sensing platforms. A brief introduction to printed electrochemical sensors and electrochemical technique analysis are presented in the first section of this review. Subsequently, sensor surface functionalization and modification techniques including drop-casting, electrodeposition, and printing of functional ink are discussed. In the next section, we review recent insights into novel fabrication methodologies, electrochemical techniques, and sensors’ performances of the most used transition metal dichalcogenides materials (such as MoS2, MoSe2 ,and WS2), MXenes, and hexagonal boron-nitride (hBN). Finally, the challenges that are faced by electrochemical printed sensors are highlighted in the conclusion. This review is not only useful to provide insights for researchers that are currently working in the related area, but also instructive to the ones new to this field.